McStrike! Framing, (Political) Opportunity and the Development of a Collective Identity: McDonald's and the UK Fast-Food Rights Campaign. (June 2022) - Royle, Tony; Rueckert, Yvonne
This article examines the development of the UK 'Fast-Food Rights Campaign' and the formation of a collective identity amongst McDonald's UK workers. It illustrates how, despite an acquiescent and fragmented workforce, workers diagnostically frame (recognize, articulate and attribute) perceived injustices relating to their pay and working conditions. However, the main focus is on prognostic framing which brings people 'together' to find a 'consensus' for a solution to perceived injustices. Prognostic framing also requires the ability to process and interpret information in a holistic way and to reach out for support to external stakeholders such as trade unions. The article applies Bourdieu's theory of capital and the concept of political opportunity to help us 'unpick' prognostic framing. In this context, it examines the cultural and social capital of worker leaders, in particular their personal characteristics, and their perceptions about the level of support in the external environment.